Pharmacoepidemiological profile and appropriateness of drug use in paediatric diarrhoea patients: a cross sectional study in western India - Chaudhari, Vipul P.; Patel, Juhi; Shah, Rima; Shah, Amit (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The background of the study was to analyze the prescribing pattern and appropriateness of drug treatment of diarrhoea. Methods: Total 194 pediatric patients with diarrhoea (140 admitted at tertiary care centre and 54 patients attended primary health care centre) were included and their demographic details; disease related parameters, drug treatment and adverse drug reactions were recorded. Appropriateness of drug treatment was analyzed using the WHO and Indian Academy of Pediatrics (IAP) guidelines for management of diarrhoea. Results: Most patients (27.32%) were less than 1 year of age and majority 54.64% were males. Most common presenting symptoms was diarrhoea with dehydration (100%) followed by vomiting (60%), fever (54.29%). Stool cultures were carried out only in 22.86% patients at tertiary health care centre while no investigations were carried out at PHC. Average number of drugs prescribed per patient was 8.25 ± 1.3. All the patients were given fluid replacement therapy. 94.29% and 85.19% patients were prescribed antimicrobials at tertiary centre (THC) and PHC respectively. Most common antibiotic used was cephalosporins (82%) followed by aminoglycosides (48.57%) of patients at THC while ofloxacin (82.60%) and metronidazole (17.40%) were commonly used at PHC. Analgesic/antipyretic was required in 70.71% and 85.19% of patients at THC and PHC respectively. Comparing with the WHO diarrhoea management guidelines and IAP guidelines, only 8 (14.81%) prescriptions were considered as rational. 2.85% patients developed mucocutaneous rash as ADR. Conclusions: Inappropriate prescribing for diarrhoea is highly prevalent in society. Emphasis on proper diagnosis and treatment, education and availability of locally effective guidelines may help in a better and judicious use of drugs in children.